A streamline solution for rigid laterally loaded piles in permafrost - Foriero, A.; Ladanyi, B. (Canadian Geotechnical Journal, 1989)
A streamline solution for the design of laterally loaded rigid piles in permafrost is presented. The proposed method relies on a power law to describe the rate dependence of permafrost creep response. It describes the soil movement with a kinematically admissible velocity field and estimates the overall reaction at a given pile section with the bound theorem for a creeping material. The approach is valid only for a secondary creep rate and a stationary state of stress. Key words: pile, lateral load, velocity field, secondary creep rate.